2010
DOI: 10.1007/bf03347058
|View full text |Cite
|
Sign up to set email alerts
|

Corneainacromegalic patientsasapossible target of growth hormone action

Abstract: Acromegaly is characterized by greater CCT values, supporting the hypothesis that GH excess may have stimulatory effects on the cornea as well as on other target organs. Higher GH levels, disease control status and duration of active disease seem to be the main causes of increased corneal thickness. We suggest a careful and detailed corneal evaluation in acromegalic patients to prevent the potential risk of increased IOP, in addition to the already-known complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
0
25
0
4
Order By: Relevance
“…In a relatively new study comparing central corneal thickness (CCT) between acromegalic patients and healthy subjects, Ciresi et al have reported higher CCT values among acromegalic patients 6. They have also reported the difference to be high enough to affect the accuracy of IOP measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In a relatively new study comparing central corneal thickness (CCT) between acromegalic patients and healthy subjects, Ciresi et al have reported higher CCT values among acromegalic patients 6. They have also reported the difference to be high enough to affect the accuracy of IOP measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is conceivable that corneal tissue is a target for GH action. It is noteworthy that Ciresi and coworkers [14] observed a strong linear correlation between CCT and GH levels in a group of 28 patients with acromegaly. Our study did not find a statistically significant correlation between CCT and GH plasma levels.…”
Section: Discussionmentioning
confidence: 87%
“…Published evidence to date has indicated that IOP is significantly increased in acromegalic patients when compared with healthy subjects [12,14,27]. Consequently, acromegaly has been considered a risk factor for glaucoma development [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the eye participates in hypophyseal pathology, especially in cases of increased secretion of GH [9,10,11] , a glaucomatous pathology in subjects with acromegaly is exceptional. The hypothesis that GH could favour the onset of POAG, formulated by Greco and coll [12] , has not found confirmation, and the finding of increased values of IOP in subjects with acromegaly, reported in the past few decades, is probably to be connected to variations in the thickness of the cornea induced by the GH, which were not taken into account.…”
mentioning
confidence: 99%